GLOBAL POLICY STUDY OF SUSTAINABLE EDUCATION (EDUCATION SUSTAINABLE DEVELOPMENT) - Nurhayati, Titi (Indonesian Journal of Adult and Community Education, 2022)
The development of human resources is inseparable from the development of human resources as a whole which must be carried out on an ongoing basis. One important factor is education. Education for All is an ideal concept developed by several countries in the context of education, but Education for Sustainable Development (ESD) has various influences. National community factors and individuals face constructive and creative global challenges and strive to promote the development of a resilient and sustainable society. Adapted to all member countries to answer the challenges of developing the industrial era 4.0 towards society in the 5.0 era. Education policy is formulated in accordance with the theoretical basis of education policy and its components. In Indonesia, the Education Policy is Presidential Decree No. 87 of 2017 Education which aims to strengthen the nation's character with noble character. This is an educational movement that is enhanced by the implementation of Enhanced Personality Education (PPK; Strengthening Character Education) and is the responsibility of educational units, families and communities